Assessing DNA methylation epialleles for human cognitive dysfunction and brain disease - Rielly, Nicholas Jude (2020)
In 2016, neurological disorders were the leading cause of disability adjusted life years (number of years lost to illness or disability) and the second leading cause of death. Extensive research has been performed on associations between genetic variants and risk for neurodegenerative diseases. Now, epigenomic processes such as DNA methylation, the addition of a methyl group to the 5th carbon of cytosine (5mC) and its oxidised derivatives (5hmC, 5fC, and 5CaC), are being increasingly studied. DNA methylation contributes to changes in cognition and ageing and has been associated with several neurodegenerative diseases such as Parkinson’s disease and Alzheimer’s disease. However, little research has focused the effect methylation at these sites may have on the regulation of gene expression.